PENGARUH INVESTASI ASING TERHADAP EKONOMI PEERDAGANGAN DAN PENDIDIKAN ISLAM MASA KESULTANAN PALEMBANG TAHUN 1724-1825 - Dewi Setyawati; Heryati Heryati; Yuliarni Yuliarni (Raudhah - Proud To Be Professional, 2023)
The Palembang Sultanate in the 17th to 19th centuries was the background for the lives of the people of Palembang. This period becomes interesting when it is connected to the world of trade because the Palembang Sultanate had collaborated with the VOC in 1642. This had an influence on the trade economic system during the time the Sultan of Palembang was in power at that time. This research uses historical methods and literature studies. The historical method has several stages, namely heuristics, source criticism, interpretation, and historiography. The aim of this research is to determine the influence of foreign investment on the trade economy of the Palembang Sultanate period 1724-1825 because at that time the Palembang Sultanate carried out trade relations, especially spices, especially pepper and tin, both domestically and abroad.